THE INFLUENCE OF LEARNING FACILITIES, TEACHER TEACHING SKILLS, AND LEARNING MOTIVATION ON STUDENT LEARNING OUTCOMES - Salsabila, Elsa; Fauzi, Achmad; Adha, Maulana Amirul (Cendikia: Jurnal Pendidikan dan Pengajaran, 2024)
This research was conducted at SMK Negeri 48 East Jakarta to determine the effect of learning facilities, teacher teaching skills, and learning motivation on learning outcomes with a survey method using a questionnaire as a research instrument. The data used in this study used quantitative data using path analysis. The data analysis technique in this study used the SmartPLS application. The population of this study were class X, XII MPLB and XII OTKP students at SMKN 48 Jakarta, namely 108 students. The sample used was 85 students with. The use of a scale in this study is a Likert scale with the data analysis used is Structural Equational Modeling-Partial Least Square (SEM-PLS) for the software used SmartPLS version 4.0. The results of this study are that there is a positive and significant influence between the learning facilities variable on student learning outcomes followed by t-statistics, namely 2.356> 1.662, and has a p-value of 0.019 <0.05. There is a positive and significant influence between the variable of teacher teaching skills on learning outcomes with t-statistics, namely 4.320> 1.662, and has a p-value of 0.000 < 0.05. and There is a positive and significant influence between the learning motivation variable on learning outcomes with t-statistics, namely 0.474> 1.662, and has a p-value of 0.000 < 0.05.